Experimental Study on Cytoflavin Pharmacological Correction of Cyclophosphamide-Induced Toxic Affections of the Liver and Kidneys - V. A. Kashuro; S. I. Glushkov; L. V. Minaeva; T. M. Novikova (Антибиотики и Химиотерапия)
The experimental data concerning the influence of repeated administration of cyclophosphamide in a total dose of 200 mg/kg on the glutathione metabolism and lipide peroxidation in the liver and kidneys of albino noninbred rats are presented. The possibility of the natural cytoprotection system correction by the use of cycloflavin was shown. The cytoprotection action mechanisms of the pharmacological agent are discussed.